Studies on the structure–property relationships and corrosion behaviour of the activated flux TIG welding of UNS S32750. (August 2016) - Ramkumar, K. Devendranath; Goutham, P. Siva; Radhakrishna, V. Sai; Tiwari, Ambuj; Anirudh, S.
Graphical abstract: Highlights: Activated flux TIG welding of Super-duplex stainless steel. Joint efficiencies of 91.6%, 87.4% and 93.06% for NiO, MoO3 and SiO2 fluxes, respectively. Oxygen analysis showed higher amount of oxygen in SiO2 and MoO3 welds. Abstract: In the present study, three different fluxes namely NiO, MoO3 and SiO2 were employed to investigate the weldability of super-duplex stainless steel (UNS S32750). Bead on trial studies were conducted to determine the effect of welding current on the depth of penetration and depth to width (D/W) ratio. The studies demonstrated that complete penetration could be achieved in a single pass with the use of activated flux. Microstructure studies showed the formation of coarser grains of ferrite along with three different types of austenite which are Widmanstätten, intra-granular and grain boundary austenite in the fusion zones of all the weldments. Oxygen content and ferrite count analysis were also carried out at the fusion zones of the weldments. Tensile studies inferred that the tensile failures occurred at the weld zone for all the cases. The joint efficiencies of the activated flux tungsten inert gas (A-TIG) weldments employing NiO, MoO3 and SiO2 flux were reported to be 91.6%, 87.4% and 93.06%, respectively. The impact toughness of the A-TIG weldments was found to be lower than that of the base metal (82 J). Potentiodynamic polarization studies were also performed to investigate the corrosion behaviour of the welds in 3.5% NaCl environment.